The Bridged Digital Artery Perforator Flap as an Alternative Reconstructive Option for Dorsal Digital or Toe Soft Tissue Defects. Issue 5 (May 2022) - Kostopoulos, Epameinondas; Konofaos, Petros; Mitchel, Matthew; Kotsakis, Ioannis; Georgopoulos, Gerasimos; Diamantopoulos, Antonios; Korfiati, Georgia; Champsas, Gregorios; Casoli, Vincent
Abstract : Background: Dorsal digital soft tissue defects are considered among the most challenging to reconstruct. Numerous treatment options are proposed, including advancement flaps, antegrade, retrograde flow flaps, adipofascial flaps, and digital artery perforator flaps. However, the optimal treatment remains controversial. The concept of the "bridge principle, " consisting of the indirect transfer of the flap to the defect area through a muscular bridge, has recently introduced by authors for medial canthal reconstruction. The aim of the study was to examine the feasibility of its application in digital reconstruction for dorsal defects and the development of a new flap. The utilization of the dorsal subcutaneous adipofascial digital or toe tissue as a "bridge" led to description and development of bridged digital artery perforator flaps as an alternative treatment of such defects. Methods: From November 2017 to September 2019, a series of 14 patients (mean age of 57.1 years) suffered from dorsal digital or toe soft tissue defects of different dimensions and sustained reconstruction with this new technique. Results: Twelve digits and 2 toes have been concerned. The mean size of the defects was 1.3 × 1.1 cm. All flaps survived without a sign of venous congestion. No functional digital or toe problems were observed during the follow-up period (mean of 11.6 months). Minor wound dehiscence presented in 2 cases (2 of 14 [14.3%]) and a transient skin swelling around the flap in 1. Conclusions: A new concept was introduced to resolve a challenging problem. Initial outcomes are very encouraging. These flaps could be a valuable and reliable reconstructive option.